Diagnóstico urodinâmico de obstrução infravesical em mulheres com distopias pélvicas - Martins, Jose Tadeu Carvalho [UNIFESP] (2021)
Objectives: This study aims to characterize the urodynamic values of urination in women with genital prolapse to identify bladder outlet obstruction. Methods: This study is about the cross-sectional, qualitative and descriptive prospective carried out at the Department of Gynecology and Obstetrics of the Hospital University Cassiano Antonio de Moraes (HUCAM- Hospital das Clínicas) of the Federal University of Espírito Santo, in partnership with the Department of Gynecology of the Federal University of São Paulo (UNIFESP), after approval of the Research Ethics Committee of UFES and board of HUCAM. Patients were selected according to previously defined inclusion and exclusion criteria and were clinically evaluated by anamneses, physical examination with the accomplishment of the POP-Q and urodynamic examination. There were comparisons with the results of the paramedics and the classification groups by Pop-Q. The first analysis was with the groups Ba and Bp “<zero”, “zero” and “>zero” in addition to C and D “zero” and “≥zero”. The second analysis was carried out between the control group (all points "<zero") and the G1 group (Ba ">zero" and the other points “≤zero”). Were considered with the OIF patients who presented RPM increased, Qmax in the FF ≤12mL / s, presence of HAD e loss on HAS, descreased CV, Qmax in the EF / P ≤12mL / s, PdetQmax in the EF / P 20cmH2O, increased RU, IC BOO intermediate and obstructive, weak ICV and Blaivas & Groutz nomogram with obstruction. Results: The pacientes of the group "more than zero" and "zero" on the isolated Ba point filled the urodinamic criteria linked in this study and were considered with OIF. The pacientes of the group “zero or more" on the Bp, C and D points suggest presence of OIF however they present more complex dystopias with more than one affected compartment. Conclusion: The urodynamic parameters listed in this study provided objective data for the diagnosis of OIF, when associated with prolapse in the anterior compartment.